Morphology of a neglected large-sized species of Geophilus from Iran (Chilopoda: Geophilidae) - Zarei, Roghaieh; Rahimian, Hassan; Bonato, Lucio (Zootaxa, 2013)
Geophilus gigas was described briefly by Attems in 1951 from two sites in Iran, but neither reported nor cited subsequently. The original description is inadequate to understand the full morphology and the taxonomic position of the species. Thus it is here redescribed and figured in detail based on the examination of a syntype and newly collected specimens. Furthermore it is compared with the most similar species of the genus Geophilus. G. gigas can be reliably distinguished from other related species for the maximum body size (more than 6 cm), the arrangement and extent of the sternal pore-fields (with additional groups of pores), the coxal pores number and distribution (tens, scattered), and the size of the ultimate legs (swollen in both sexes).